Preliminary Plant Design Of Chloroform From Acetone And Bleaching Powder Capacity 40,000 Tonnes Per Year - HAKIM, Muhammad Fahmi, M. Mujiburohman, S.T., M.T., Ph.D, Emi Erawati, S.T., M.Eng (2015)
Chloroform is one of industries have been good prospect. For need chloroform, Indonesia still importing from the other countries. Chloroform used as an anesthetic and a non-polar solvent in laboratories or by industries. From many factors as the availbillity of raw materials, transportation, need of chloroform in Indonesia and overseas, can determine optimum capacity to produce chloroform is 40,000 tonnes/year. With reacted between bleaching powder and aceton in ratio 27,522 kg of acetone and 2,752 kg of bleaching powder in batch reactor (T=50℃ and P=1 atm) during 2 hours, will produce chloroform and byproducts like as calcium acetate Ca(CH3COO)2, calcium hydroxide (Ca(OH)2), calcium chloride (CaCl2). Plant will be build at 2017 in Cilegon,Banten with area is 52,332 m2. total of water needs is 278 m3/hours, steam required is 2,693.886 kg/h,for electricity is 542 KW,fuel requirement is 82.79 L/h. The economic analysis concludes that fixed manufacturing cost (Fa) is 1,845,139,452,209. Variable cost (Va) is 16,510,294,893,475. Regulated cost (Ra) is 16,822,580,694,015. Selling product (Sa) is 41,325,887,664,951. ROI (Return on Investment) before and after tax are 99.95% and 69.97%. POT (Pay OutTime) before and after tax are 0.91 years and 1.25 years. BEP is 52.58 % and. So if this plant will be build so many advantages and very profitably.